Comparison of two approaches to measuring change in health status in rheumatoid arthritis: the Health Assessment Questionnaire (HAQ) and modified HAQ. Issue 11 (November 1992) - Ziebland, S; Fitzpatrick, R; Jenkinson, C; Mowat, A; Mowat, A
Abstract : As an alternative to the calculation of change scores for health status questionnaires used in clinical trials or longitudinal studies, transitional questions have been developed for patients to assess changes directly themselves. Here the original Health Assessment Questionnaire (HAQ) is compared with a modified version of the HAQ (MHAQ) which contains transition questions used at follow up. These, together with a set of standard rheumatological tests, were all completed by 100 patients with rheumatoid arthritis on two occasions, three months apart. Change scores were calculated for the HAQ and for the clinical measures and compared with the MHAQ. The results were strikingly in favour of encouraging patients to assess their own degree of change through the use of transition questions in the MHAQ.